2019
DOI: 10.1186/s12985-019-1256-z
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial IL-8 induced by porcine circovirus type 2 affects dendritic cell maturation and antigen-presenting function

Abstract: BackgroundPorcine circovirus (PCV) disease caused by PCV type 2 (PCV2) is mainly attributed to immunosuppression and immune damage. PCV2 can infect vascular endothelial cells and induce high expression of endothelial IL-8. Dendritic cells (DCs), as professional antigen-presenting cells, can not only present antigens but also activate naïve T-cells, causing an immune response.MethodsTo demonstrate whether endothelial IL-8 is the main factor inhibiting the maturation and related functions of dendritic cells duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It is reported that endothelial-derived IL-8, with a pentapeptide AVLPR extension at the NH2-terminus [5], has different biological function compared with monocyte-derived IL-8 [6]. Our previous reports also showed that the endothelial IL-8 upregulated by PCV2 infection could inhibit the maturation and antigen presentation of dendritic cells [4,7].…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that endothelial-derived IL-8, with a pentapeptide AVLPR extension at the NH2-terminus [5], has different biological function compared with monocyte-derived IL-8 [6]. Our previous reports also showed that the endothelial IL-8 upregulated by PCV2 infection could inhibit the maturation and antigen presentation of dendritic cells [4,7].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that ANXA1 is either upregulated in tumours such as gastric cancer, 17 , 18 , 19 , 20 pancreatic carcinoma 21 and lung cancer 22 and correlated with poor prognosis or downregulated in tumours such as head and neck squamous cell carcinoma 23 and nasopharyngeal carcinoma. 24 Typically, studies have focused on the effects of ANXA1 binding to the FPR receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, IL‐8 gene expression is regulated by the transcriptional activation of nuclear factor‐kB (NF‐κB), which is suggested to be mainly associated with the binding between the minimal promoter region of IL‐8 and the p65 or cRel homodimers of NF‐κB 15,16 . Recently, it was found that IL‐8 could affect dendritic cell (DC) maturation by retaining DCs in tumours and blocking the migration capacity of DCs from initial inflammation sites to draining lymph nodes, affecting its antigen‐presenting function in tumours 17–19 . Based on the literature and previous reports, we hypothesized that NF‐κB (p65) hyperactivation mediated by ANXA1 is partly responsible for IL‐8 overexpression, which inhibits DC maturation in GBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, PCV2 enhances the expression of the suppressor of cytokine signaling 3 (SOCS3), which further interacts with STAT3 and TNF-associated receptor-associated factor 2 (TRAF2), resulting in subclinical infection characterized by downregulation of IL-6 and TNF-α signaling [ 142 ]. Furthermore, PCV2-induced endothelial IL-8 decreases the adhesion and migration of monocyte-derived DCs (MoDCs), resulting in a decrease in the maturation rate of MoDCs and further inhibition of antigen presentation by dendritic cells (DCs) [ 143 ]. Moreover, the PKR signaling pathway was activated by dsRNA generated during PCV transcription, which activates eIF2α to inhibit virus protein [ 70 , 144 ].…”
Section: Crosstalk Between Pcv and Hostmentioning
confidence: 99%